Political Legitimization without Morality? - Kühnelt, Jörg (Springer, 2017)
The initial idea for this anthology arose during my work at the interdisciplinary Collaborative Research Centre (SFB) 485 Norm and Symbol at the University of Konstanz. My research project on the potential of Hobbesian contract theory was in?uenced by the focus of the SFB on social phenomena such as pluralism and cultural change. In this context, I realized that the Hobbesian idea to refer only to instrumental rationality and basic egoistic interests to legitimize a state has, on one hand some advantages for pluralistic societies: All individuals are supposed to share these premises independent of the personal values they might hold. On the other hand, a rational legitimization must cope with the fundamental problem of explaining and legitimizing those tasks of legal states that go beyond the idea of a minimal state. Although my research was focused on the idea of solving this problem with a modi?cation of the Hobbesian argument, I became interested in the more general question of which role morality could or should play in legitimizing a state. Within the current discussion, not only rational but also political accounts of legitimacy can be attractive as soon as they try to avoid contentious normative premises. To analyse some of the core ideas within the current discussion, I - ganized an interdisciplinary workshop at the University of Konstanz in December 2004 in which different perspectives from sociology, politics and philosophy were compared and analysed.